Pemanfaatan Tanaman Bambu untuk Membuat Lampu Hias di Desa Bondawuna Kecamatan Suwawa Kabupaten Bone Bolango - Irvan Salihi; Zohrahayaty Zohrahayaty; Swastiani Dunggio; Syahrir Abdussamad (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2023)
Community service activities in the form of Thematic Real Work Lectures carried out by Ichsan Gorontalo University students located in Bondawuna Village, Suwawa District, Bone Bolango Regency are one of the activities carried out in this village. This activity program was chosen based on the problems of partners who still lack guidance in utilizing natural resources in the form of bamboo trees which can be processed into decorative lighting products so that they can increase the income of the surrounding community. The method given in this service is partners who are given training and hands-on practice on how to process and make decorative lamps from bamboo. The manufacturing process starts with selecting bamboo trees to be used as decorative lighting products, after which the bamboo is cleaned and then cut and mashed according to the size for the decorative lighting products. After that, the process of installing lights and cables and painting the product. The final result of the assembly obtained is the existence of decorative lighting products made of bamboo material which can be used as decorative lamps for bedrooms and living rooms that look minimalist